2004
DOI: 10.1016/j.visres.2004.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Texture segregation in traumatic brain injury––a VEP study

Abstract: Visual evoked potentials (VEPs) were recorded to textures segregated by gradients in orientation or motion. Recordings were obtained in traumatic brain-injured (TBI) subjects and in normal controls. We analyzed both the low-level VEPs (llVEPs) evoked by homogenous stimuli, as well as the components associated with texture segregation (tsVEP) obtained through an appropriate linear combination. Our results suggest that the tsVEP, presumably higher up in the visual processing chain than the llVEP, is sensitive to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…By analysing low-level VEPs evoked by stimuli with an homogenous motion or orientation pattern in comparison to stimuli of greater complexity (i.e. textured stimuli) Lachapelle et al (2004) found that VEP peak times to homogenous stimuli did not differ between TBI patients and controls but peak times were longer to textured stimuli in TBI patients than controls. These findings suggest that TBI patients show spared first-order visual processing (restricted to area V1 of visual cortex) but impaired higher order visual processing mechanisms that may originate from second-order antero-posterior cortical processes higher in the visual processing chain.…”
Section: Processing Speedmentioning
confidence: 95%
See 1 more Smart Citation
“…By analysing low-level VEPs evoked by stimuli with an homogenous motion or orientation pattern in comparison to stimuli of greater complexity (i.e. textured stimuli) Lachapelle et al (2004) found that VEP peak times to homogenous stimuli did not differ between TBI patients and controls but peak times were longer to textured stimuli in TBI patients than controls. These findings suggest that TBI patients show spared first-order visual processing (restricted to area V1 of visual cortex) but impaired higher order visual processing mechanisms that may originate from second-order antero-posterior cortical processes higher in the visual processing chain.…”
Section: Processing Speedmentioning
confidence: 95%
“…In contrast to the aforementioned experiments that have used putative input-output paradigms to understand processing speed deficits in TBI, simple and more complex Visual Evoked Potential (VEP) markers, in the absence of response output information, can reveal further information as to the nature of possible information processing deficits in TBI (Lachapelle et al, 2008(Lachapelle et al, , 2004). By analysing low-level VEPs evoked by stimuli with an homogenous motion or orientation pattern in comparison to stimuli of greater complexity (i.e.…”
Section: Processing Speedmentioning
confidence: 99%
“…Given that tsVEPs require more neuronal time to be processed compared to llVEPs, we believe that their use would add valuable knowledge to the evaluation of the integrity of the global information processing of the brain, particularly in the presence of developmental or acquired injuries which are diffuse by nature and which often affect the processing of visual information due to the localization and organization of the visual pathways in the brain (i.e., perinatal brain hemorrhages due to prematurity, traumatic brain injury, etc.) [26]. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1e). As a result, the activation associated with the lower-level processing was suppressed and the resulting negative wave, a difference potential, reflects only the tsVEP response (Arcand et al, 2007;Bach & Meigen, 1992;Bach et al, 2000;Lachapelle et al, 2004). For each oriVEP, texVEP and tsVEP waveform obtained for each participant, the N2 peak (or the texture-segregation N2 in the case of the subtraction) was identified for the electrode sites O1, O2 and Oz using semi-automatic detection.…”
Section: Discussionmentioning
confidence: 99%
“…This component originates from the V1 area and is thought to reflect combination of information from V2 and V3 associative visual areas through feedback connection circuits (Scholte et al, 2008). Therefore, tsVEPs give an intermediary measure of visual processing between lower-level VEPs, which peak at around 100 ms, and cognitive event-related responses, which usually peak after 300 ms after stimulus appearance (Lachapelle et al, 2004).…”
Section: Introductionmentioning
confidence: 99%